Early Trypanosoma cruzi Infection Reprograms Human Epithelial Cells. (9th April 2014) - Chiribao, María Laura; Libisch, Gabriela; Parodi-Talice, Adriana; Robello, Carlos
Abstract : Trypanosoma cruzi, the causative agent of Chagas disease, has the peculiarity, when compared with other intracellular parasites, that it is able to invade almost any type of cell. This property makes Chagas a complex parasitic disease in terms of prophylaxis and therapeutics. The identification of key host cellular factors that play a role in the T. cruzi invasion is important for the understanding of disease pathogenesis. In Chagas disease, most of the focus is on the response of macrophages and cardiomyocytes, since they are responsible for host defenses and cardiac lesions, respectively. In the present work, we studied the early response to infection of T. cruzi in human epithelial cells, which constitute the first barrier for establishment of infection. These studies identified up to 1700 significantly altered genes regulated by the immediate infection. The global analysis indicates that cells are literally reprogrammed by T. cruzi, which affects cellular stress responses (neutrophil chemotaxis, DNA damage response), a great number of transcription factors (including the majority of NF κ B family members), and host metabolism (cholesterol, fatty acids, and phospholipids). These results raise the possibility that early host cell reprogramming is exploited by the parasite to establish the initial infection and posterior systemic dissemination.